Jilbab Sebagai Ibadah (Studi Fenomenologi pada Polisi Wanita Polres Baubau) - fitrysaleh, adheyatul (DIKTUM: Jurnal Syariah dan Hukum, 2019)
In Islamic law, wearing headscarves is obligatory for Muslim women. Each use is based on several motivations, one of them is worship as the main motivation. Based on the command of al-Qur’an dan sunnah, the implementation is worth worship. Headscarves are in their real positionthat has been legitimized, also as honor and glory not to bring down humanity and reduce dignity, precisely for policewomen can add energetic, professional in the ministry, and continue to serve well.Kapolri regulations regarding headscarves are only permissible not be a necessity that is adhered to within the scope of the police. From the policy it was assessed that policewomen wearing headscarves were based on the awareness of individuals had specifications of reasons as religious orders, moreover there is no intervention and coercion from any other party and then reasons for wearing the headscrarf followed by other motivations.